Web Based Task Management System Integrating the Pomodoro Technique with Productivity Analytics - Syafrial Fachri Pane; Muhammad Baihaqi Siregar; Zidan Ardiansyah; Muhammad Amran Hakim Siregar (NUANSA INFORMATIKA, 2026)
Effective time management plays a crucial role in maintaining academic productivity among university students. However, increasing academic workloads and digital distractions often make it difficult for students to maintain consistent focus while completing their tasks. Although numerous task management and Pomodoro-based applications exist, most tools address either task organization or timed focus sessions in isolation, without integrating both functionalities into a unified productivity monitoring system. This research gap motivates the development of a system that combines structured time management with data-driven productivity analytics, which is not found in widely used tools such as Todoist or standard Pomodoro timers. This study proposes a web-based task management system that integrates the Pomodoro Technique with productivity analytics to support structured productivity monitoring. The proposed system was evaluated using activity data from recorded focus sessions comprising 120 Pomodoro sessions across a four-week observation period. The productivity aggregation model achieved a task completion rate of 78.3%, with an average daily focus duration of 142 minutes. The system successfully processed all recorded sessions without data discrepancies, and trend visualizations confirmed consistent productivity improvements over the observation period. The results show that the integrated Pomodoro–analytics approach effectively transforms recorded focus session data into measurable productivity indicators, achieving a 78.3% task completion rate and an average daily focus duration of 142 minutes across 120 sessions the integrated system into a scientifically measurable and structured productivity monitoring tool, distinguishing it from existing standalone task managers and Pomodoro applications through its unified analytics capability.